1992
DOI: 10.1002/art.1780350506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for the presence of chlamydia in the synovium of patients with reiter's syndrome

Abstract: Objective. There is much evidence indicating that chlamydial antigens in the synovium may be critical in the pathogenesis of Reiter's syndrome (RS), but it is not known whether intact organisms are present in that tissue in any stage of the disease. The present study was undertaken to begin to address this question.Methods. We used a highly specific and sensitive molecular hybridization screening system which detects chlamydial RNA, to examine synovial biopsy samples from 22 patients with various arthropathies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(45 citation statements)
references
References 33 publications
(24 reference statements)
1
42
0
2
Order By: Relevance
“…Nucleic acids were extracted from biopsy samples and SF pellets as previously described (6). Briefly, frozen samples were homogenized in a Dounce containing 0.5 ml of buffer (25 mM Tris, pH 8, 10 mM EDTA, 100 m M NaC1,0.5% sodium dodecyl sulfate) and 1 ml of buffered phenol at 65°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleic acids were extracted from biopsy samples and SF pellets as previously described (6). Briefly, frozen samples were homogenized in a Dounce containing 0.5 ml of buffer (25 mM Tris, pH 8, 10 mM EDTA, 100 m M NaC1,0.5% sodium dodecyl sulfate) and 1 ml of buffered phenol at 65°C.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, an infectious etiology for some forms of reactive arthritis (ReA) has long been postulated, and C trachomatis has emerged as a prominent agent among organisms associated with the disease (43). Despite evidence linking ReA with chlamydial infection, however, it is not clear whether the process leading to the disease involves viable bacteria in the synovium at some point or whether the disease is purely immune-mediated in response to chlamydial antigenic debris at the synovial site (5)(6)(7).…”
mentioning
confidence: 99%
“…Chlamydia1 hsp57 has been identified as the immunodominant protein for a CD4 T cell response of guinea pigs after infection of the eye, which leads to hypersensitivity to chlamydial antigen (23), a situation resembling that in reactive arthritis (47). Furthermore, Chlamydia-derived hsp57 peptides that are able to bind to HLA-B27 have recently been characterized (48).…”
Section: Discussionmentioning
confidence: 99%
“…(10), however, these recurrences are generally not related to overt genitourinary infections (11). It was also reported that about 43% of RS patients with recurrent attacks showed no discriminate urethritis infection (12 (13). The nature of such persistent chlamydial infection was studied by several groups (14,15 …”
Section: F I G U R E 3 T H E C L I N I C a L C O U R S E O F T H E mentioning
confidence: 99%